Which growth charts to use to classify neonates as small-for-gestational age at birth? - Anand, Pratima; Sahoo, Tanushree; Gulla, Krishna Mohan (Indian Journal of Child Health, 2019)
The use of correct growth chart at birth is crucial to identify small-for-gestational age (SGA) neonates since the burden of SGA is an indicator of national health status and hence has programmatic implications. With multitude of charts available globally and in context of recent introduction of newer standard charts (Intergrowth-21st), it is important to understand the merits and demerits of different types of neonatal charts in clinical application. The current review summarizes the available growth charts and discusses the advantages and disadvantages of each of them. We conclude that most of the available growth charts either overestimate or underestimate the neonatal growth, both of which are unacceptable. Hence, it is essential to devise region specific growth charts. In case of unavailability of the regional growth charts, the global charts should be used cautiously.